Reactive Plasma N-Doping of Amorphous Carbon Electrodes: Decoupling Disorder and Chemical Effects on Capacitive and Electrocatalytic Performance - Hoque, Md. Khairul; Behan, James A.; Creel, James; Lunney, James G.; Perova, Tatiana S.; Colavita, Paula E. (Frontiers in Chemistry, 2020)
Nitrogen-free amorphous carbon thin films prepared via sputtering followed by graphitization, were used as precursor materials for the creation of N-doped carbon electrodes with varying degrees of amorphization. Incorporation of N-sites was achieved via nitrogen plasma treatments which resulted in both surface functionalization and amorphization of the carbon electrode materials. X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy were used to monitor composition and carbon organization: results indicate incorporation of predominantly pyrrolic-N sites after relatively short treatment cycles (5 min or less), accompanied by an initial etching of amorphous regions followed by a slower process of amorphization of graphitized clusters. By leveraging the difference in the rate of these two processes it was possible to investigate the effects of chemical N-sites and C-defect sites on their electrochemical response. The materials were tested as metal-free electrocatalysts in the oxygen reduction reaction (ORR) in alkaline conditions. We find that the introduction of predominantly pyrrolic-N sites via plasma modification results in improvements in selectivity in the ORR, relative to the nitrogen-free precursor material. Introduction of defects through prolonged plasma exposure has a more pronounced and beneficial effect on ORR descriptors than introduction of N-sites alone, leading to both increased onset potentials and reduced hydroperoxide yields relative to the nitrogen-free carbon material. Our results suggest that increased structural disorder/heterogeneity results in the introduction of carbon sites that might either serve as main activity sites, or that enhance the effects of N-functionalities in the ORR via synergistic effects.